Teologi Rasional: Telaah atas Pemikiran Kalam Muhammad Abduh - Makrum Makrum (Universitas Islam Negeri Mataram, 2009)
The main factor that brings Muslims backwardness is resistance to change which so called in Arabic term as jumûd, means frozen state. When Muslims were trapped under such conditions a prominent reformer, Muhammad Abduh, came to reform Islamic thoughts of the divine. This paper attempt to examine his thought about God that made him popularly known as rational theologians and neo-Mu'tazilite. The style of Abduh’s rationalism is indicated in his very high appreciate to intellect. Intellect in Abduh’s view is not only able to know four things (God, obligations to God, good and bad, and the obligation to do good and avoid bad deeds) as in the Mu'tazilite theology, but also capable of knowing the existence of life-happiness and misery in the Hereafter, and making the laws. He even stated that intellect is also able to know the nature of God’s characters, though not all of them.